Corruption-Driven Inequalities in Access to Adult Education. Issue 4 (November 2022) - Gerganov, Alexander; Ilieva-Trichkova, Petya; Boyadjieva, Pepka
The article aims to show that taking into account diverse characteristics of the wider social environment is indispensable for a better understanding of participation in adult education (PAE). It explores the association of corruption as a macro factor with PAE, arguing for an integrated approach to PAE. By using two indexes for corruption at country level Corruption Perception Index and the Index of Public Integrity—and micro-data for adults aged 25–64 from 29 European countries in the Adult Education Survey, 2016, as well as by applying random-effects logit models, this study has demonstrated that a country's higher corruption level is associated with the lower probability of PAE. Our article also reveals that the relationships between individual-level variables such as gender, higher education, social background, and PAE are embedded in a wider social milieu, and corruption is an essential characteristic of that milieu which deepens some of the inequalities in PAE.